Pengaruh Penggunaan Media Pembelajaran Digital terhadap Hasil Belajar Siswa - Dewi Fitri Yeni; Desi Rahmatika; Muriani Muriani; Desi Armi Eka Putri (Fakultas Tarbiyah Institut Pesantren Sunan Drajat Lamongan, 2023)
The purpose of this study is to be able to determine the effect of using media on student learning outcomes as well as researchers so that they can create fun and interesting student learning situations. The effect of using digital learning media on student learning outcomes is a qualitative research method. The author uses a research method in the form of Literature Review or literature review. If the media carries messages or information that is instructional or contains learning purposes, then the media is called learning media. but what is necessary from the teaching objectives that have been formulated. With that learning objectives should be used as a reference for the use of learning media